Conditional Effects of Lifetime Alcohol Consumption on Methamphetamine-Associated Neurocognitive Performance. (10th June 2019) - Saloner, Rowan; Paolillo, Emily W.; Umlauf, Anya; Moore, David J.; Heaton, Robert K.; Grant, Igor; Cherner, Mariana
Abstract: Objectives: Methamphetamine (MA) dependence contributes to neurotoxicity and neurocognitive deficits. Although combined alcohol and MA misuse is common, how alcohol consumption relates to neurocognitive performance among MA users remains unclear. We hypothesized that alcohol and MA use would synergistically diminish neurocognitive functioning, such that greater reported alcohol consumption would exert larger negative effects on neurocognition among MA-dependent individuals compared to MA-nonusing persons. Methods: Eighty-seven MA-dependent (MA+) and 114 MA-nonusing (MA−) adults underwent neuropsychological and substance use assessments. Linear and logistic regressions examined the interaction between MA status and lifetime average drinks per drinking day on demographically corrected global neurocognitive T scores and impairment rates, controlling for recent alcohol use, lifetime cannabis use, WRAT reading performance, and lifetime depression. Results: MA+ displayed moderately higher rates of impairment and lower T scores compared to MA−. Lifetime alcohol use significantly interacted with MA status to predict global impairment (ORR = 0.70, p = .003) such that greater lifetime alcohol use increased likelihood of impairment in MA−, but decreased likelihood of impairment in MA+. Greater lifetime alcohol use predicted poorer global T scores among MA− ( b = −0.44, p = .030) but not MA+ ( b = 0.08, p = .586). Conclusions: Contrary to expectations, greater lifetime alcohol use related to reduced risk of neurocognitive impairment among MA users. Findings are supported by prior research identifying neurobiological mechanisms by which alcohol may attenuate stimulant-driven vasoconstriction and brain thermotoxicity. Replication and examination of neurophysiologic mechanisms underlying alcohol use in the context of MA dependence are warranted to elucidate whether alcohol confers a degree of neuroprotection.